2014
DOI: 10.1007/s00404-014-3304-7
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of maternal and neonatal outcomes of pregnancy with mental disorders: results of an analysis using propensity score-based weighting

Abstract: Maternal mental disorders were associated with adverse birth outcomes and socioeconomic disadvantage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…We used electronic medical records to identify maternal psychiatric disorders, and as such, we may be subject to underreporting of psychiatric disorders compared to studies with interview data [36]. Our observed association between psychiatric disorders and preterm birth <37 weeks' gestation was also smaller than that found in other studies [16,18], also supporting the notion of underreporting of psychiatric disorders in our obstetric population. Therefore our results can be considered to be conservative.…”
Section: Discussionsupporting
confidence: 65%
“…We used electronic medical records to identify maternal psychiatric disorders, and as such, we may be subject to underreporting of psychiatric disorders compared to studies with interview data [36]. Our observed association between psychiatric disorders and preterm birth <37 weeks' gestation was also smaller than that found in other studies [16,18], also supporting the notion of underreporting of psychiatric disorders in our obstetric population. Therefore our results can be considered to be conservative.…”
Section: Discussionsupporting
confidence: 65%
“…There was significant variability of the prevalence of personality disorder within the studies, specifically, 0.012% [59], 0.00764% [60], 0.3% [41], 0.857% [61], and 2.193% [26]. The overall prevalence rate of personality disorder (combining the five studies) is 0.013% (95% CI: 0.012-0.014%).…”
Section: Prevalence Rates Of Personality Disordermentioning
confidence: 93%
“…Five studies were included in this systematic review and meta-analysis [26,41,[59][60][61]. From the included studies, 1114 women were identified as having a personality disorder and 8,527,780 women formed the control group.…”
Section: Study Summarymentioning
confidence: 99%
See 2 more Smart Citations